Radiographic evaluation of tracheal collapse in dogs by compressive technique - K.G. Beltrán; J.P.E. Pascon; M.L.A. Mistieri (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2020)
ABSTRACT The purpose of this study was to verify the applicability of the compressive radiographic technique (pressures of 5, 10, 15 and 20mmHg) in the diagnosis of tracheal collapse in small breed dogs, in lateral cervicothoracic radiography. Out of the 50 dogs evaluated, 25 presented tracheal collapse (TG group), 23 did not present tracheal collapse (CG) and two were excluded because they did not tolerate a pressure of 20 mmHg. The TG group presented a smaller internal diameter of the trachea in the region of the fourth cervical vertebra (D4) and at the entrance of the thorax (TDE) compared to the CG group, in all the radiographic projections performed, as well as within the TG group where the compressive technique differed from conventional. Furthermore, there was a correlation between the clinical sign of coughing during cervical collar use and the presence of radiographic tracheal collapse at a pressure of 20 mmHg. It was concluded that the compressive radiographic technique was feasible and efficient in confirming the diagnosis of tracheal collapse in dogs, especially in the pressure of 20 mmHg, where it was associated with clinical signs, and can be used in isolation or complementary to the conventional technique.